Development of Quality Control Method for Glucofarmaka Antidiabetic Jamu by HPLC Fingerprint Analysis - Hanifullah Habibie; Rudi Heryanto; Mohamad Rafi; Latifah Kosim Darusman (Universitas Gadjah Mada, 2017)
Herbal medicines become increasingly popular all over the world for preventive and therapeutic purposes. Quality control of herbal medicines is important to make sure their safety and efficacy. Chromatographic fingerprinting has been accepted by the World Health Organization as one reliable strategy for quality control method in herbal medicines. In this study, high-performance liquid chromatography fingerprint analysis was developed as a quality control method for glucofarmaka antidiabetic jamu. The optimum fingerprint chromatogram were obtained using C18 as the stationary phase and linear gradient elution using 10–95% acetonitrile:water as the mobile phase within 60 minutes of elution and detection at 210 nm. About 20 peaks were detected and could be used as fingerprint of glucofarmaka jamu. To evaluate the analytical performance of the method, we determined the precision, reproducibility, and stability. The result of the analytical performance showed reliable results. The proposed method could be used as a quality control method for glucofarmaka antidiabetic jamu and also for its raw materials.